Hydrogen gas and biochar production from kitchen food waste through dark fermentation and pyrolysis - Pradhan, Snigdhendubala; Yuzer, Burak; Bicer, Yusuf; McKay, Gordon; Al-Ansari, Tareq (Frontiers in Chemical Engineering, 2024)
The transportation and consumption of kitchen food waste is a major contribution to greenhouse gas (GHG) emissions in global warming. To reduce this risk, it is important to recycle food waste into energy production and agricultural byproduct for nutrient management. Dark fermentation is one of the most suitable nutrient recovery techniques for generating hydrogen (H2) gas and serves as a clean energy carrier for a sustainable environment. Potatoes (Solanum tuberosum L.) and watermelon (Citrullus lanatus) are an important vegetable and fruit in demand in markets worldwide. Each year, almost 8,000 kilotons of potato peel is generated, with a GHG emission of 5 million tons of carbon dioxide (CO2) equivalent. More than 90% of watermelon rind is considered waste and is discarded. A small-scale preliminary study was conducted on these two waste products to produce H2 gas from potato peel, watermelon rind, and a mixture of peel and rind by the dark fermentation process. After volume analysis of the H2 gas produced, the remaining residue was used to produce biochar. The highest volume of 149 mL H2 gas was achieved from the peel, followed by 140 mL and 135 mL of H2 gas from the rind and the mixture of peel and rind, respectively, with a biomass pH of 4.7–5.6 and volatile solids (VS) of 77%–88%. The biochar produced from all the sample types was alkaline in nature with a pH of 7.88 ± 0.33, electrical conductivity of 0.38 ± 0.03 mS/cm, zeta potential of −25.12 ± 0.32 mV, and had a nutrient richness that could be beneficial for soil quality improvement and plant growth. However, the outcomes of this small-scale analysis cycle requires additional analytical outcomes with field application that targets the future scope of research on sustainable H2 production and agricultural application.